Comprehensive physiological, transcriptomic, and metabolomic analyses reveal the synergistic mechanism of Bacillus pumilus G5 combined with silicon alleviate oxidative stress in drought-stressed Glycyrrhiza uralensis Fisch. - Ma, Xin; Xu, Zhanchao; Lang, Duoyong; Zhou, Li; Zhang, Wenjin; Zhang, Xinhui (Frontiers in Plant Science, 2022)
Glycyrrhiza uralensis Fisch. is often cultivated in arid, semiarid, and salt-affected regions that suffer from drought stress, which leads to the accumulation of reactive oxygen species (ROS) in G. uralensis, thus causing oxidative stress. Plant growth-promoting bacteria (PGPB) and silicon (Si) have been widely reported to be beneficial in improving plant tolerance to drought stress by maintaining plant ROS homeostasis. Herein, combining physiological, transcriptomic and metabolomic analysis, we investigated the responses of the antioxidant system to Bacillus pumilus (G5) or/and Si in G. uralensis seedlings under drought stress. Results showed that drought stress caused the overproduction of ROS accompanied by the low efficiency of antioxidants [superoxide dismutase (SOD), catalase (CAT), peroxidases (POD), ascorbate (AsA)-glutathione (GSH) pool, total carotenoids, and total flavonoids]. Inversely, supplementation with the G5 or/and Si enhanced the antioxidant defense system in drought-stressed G. uralensis seedlings, and the complex regulation of G5 combined Si differ from G5 or Si individually. G5 combined Si enhanced the antioxidant enzyme system, accelerated the AsA-GSH cycle, and triggered carotenoids and flavonoids metabolism, which acted in combination via different pathways to eliminate excess ROS induced by drought stress, thereby alleviating oxidative stress. These findings provide new insights into the comparative and synergistic role of PGPB and Si in the antioxidation system of plants exposed to drought, and a guide for the application of PGPB combined Si to modulate plant stress tolerance.